Encyclopedia of industrial and organizational psychology - Rogelberg, Steven G. (Gale virtual reference library, 2007)
A thorough overview of the cross-disciplinary field of industrial and organizational psychology for students, researchers, and professionals in the areas of psychology, business, management, and human resources. In two volumes, readers are provided with state-of-the-art research and ready-to-use facts.